Демонічний світ у словесній символіці вигукових фразеологізмів української та словацької мов: перекладознавчий зіставний аспекти - Кузь, Галина (My University, 2022)
The author studies the layer of exclamatory idioms containing names of de- monological beings in Ukrainian and Slovak. The aim of the paper is a comparative and translation analysis of the selected group of phrases in the context of their ethnolinguistic and functional features. The analyzed phraseology of both languages has much in common and shows that the world of the Slavs included characters of different levels, and interaction with them was carried out through verbal magic. The difficulty of translating exclamatory idioms appears due to their semantic and expressive diffusion. The problem of translating exclamatory phraseology lies in the reproduction of the linguistic and cultural aspect of the content as well as emotional, expressive and pragmatic features. The best way of rendering is to use a substitute, among numerous variants existing in the languages compared.
Słowiańszczyzna dawniej i dziś – język, literatura, kultura. Monografia ze studiów slawistycznych
Keywords: exclamatory idiom; demonology; Ukrainian-Slovak translation; emotional and expressive specificity; pragmatic features